To Europe or Not to Europe? Migration and Public Support for Joining the European Union in the Western Balkans - Artjoms Ivlevs; Roswitha M. King (Institute of Labor Economics (IZA), 2019)
For decades, countries aspiring to join the European Union (EU) have been linked to it through migration. Yet little is known about how migration affects individual support for joining the EU in prospective member states. We explore the relationship between migration and support for EU accession in the Western Balkans. Using data from the Gallup Balkan Monitor survey, we find that prospective and return migrants, as well as people with relatives abroad, are more likely to vote favourably in a hypothetical EU referendum. At the same time, only people with relatives abroad are more likely to consider EU membership a good thing. Our results suggest that migration affects attitudes toward joining the EU principally through instrumental/utilitarian motives, with channels related to information and cosmopolitanism playing only a minor role. Overall, our study suggests that migration fosters support for joining a supranational organization in the migrants' countries of origin, which, in turn, is likely to affect political and institutional development of these countries.
Keywords: F22; F24; J61; O52; 330; migration; return migration; European Union; european integration; Western Balkans